2012
DOI: 10.1134/s1063785012060223
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the onset of instability of triple shock configurations in steady supersonic gas flows

Abstract: Three and two shock wave configurations play a determining role in all problems of both internal and external aerodynamics. These shock wave configura tions appear, e.g., at the entrance of air inlets during supersonic flight and at the exit of supersonic nozzles operating in overexpanded regimes. Previously [1][2][3], we have demonstrated for gas flows at large Mach numbers and small adiabatic indices γ that, in addition to the well known regular and nonregular (Mach type) reflection, there must exist a new t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In this case, detonation polar (11) degenerates to a point " * " (see Figures 2a-c and 4), which corresponds to the critical flow velocity behind the normal detonation wave (it means that M III = 1). A further increase in pulsed energy release leads to the loss of the stability of the shock j 3 and of the triple configuration as a whole.…”
Section: Model and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, detonation polar (11) degenerates to a point " * " (see Figures 2a-c and 4), which corresponds to the critical flow velocity behind the normal detonation wave (it means that M III = 1). A further increase in pulsed energy release leads to the loss of the stability of the shock j 3 and of the triple configuration as a whole.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Relation (11) describes so-called detonation shock polar, whose name suggests that the pulsed energy release at the shock or in the immediate vicinity of it occurs as a result of detonation initiated by a sudden increase in temperature on the shock surface. Figure 2a-c demonstrates a family of detonation polars IIIa-IIIf, which correspond to the effective adiabatic index γ 3 = γ 12 = 1.4 and different values of pulsed energy release.…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b) exists at the beginning of the flow considered (x ¼ 0). This slipstream can occur, in particular, at the Mach reflection of another interaction of the shocks that form the triple configuration [6][7][8]. The slipstream τ divides the flow regions 1 and 2.…”
Section: Model Of the Interactionmentioning
confidence: 98%
“…Additionally, in the case of unsteady interaction of shock waves with plane surfaces, the decrease of the ratio of specific heats has been shown to lead to the appearance of a significant flow reconstruction connected with the formation of the double Mach reflection. Recently it has been found that, for a flow around a system of two wedges (a model of an intake) for the Mach numbers higher than 3 and γ < 1.4 it is possible for the oscillation flow mode to appear and destroy the steady flow mode [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%